If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -7 = -2x + 9 Reorder the terms: -7 + 4x = -2x + 9 Reorder the terms: -7 + 4x = 9 + -2x Solving -7 + 4x = 9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -7 + 4x + 2x = 9 + -2x + 2x Combine like terms: 4x + 2x = 6x -7 + 6x = 9 + -2x + 2x Combine like terms: -2x + 2x = 0 -7 + 6x = 9 + 0 -7 + 6x = 9 Add '7' to each side of the equation. -7 + 7 + 6x = 9 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 9 + 7 6x = 9 + 7 Combine like terms: 9 + 7 = 16 6x = 16 Divide each side by '6'. x = 2.666666667 Simplifying x = 2.666666667
| -3=-31+16.666 | | 0.10(m-100)+15+20=0.05m+40 | | 7t=6 | | 2x-19+3x+6+2x-10=180 | | 17k^2+119k=0 | | 9a-4=14 | | 4x=5y+6 | | A/6=-18 | | -3+9=-21 | | 2a+x=7 | | 3x+(-15+3x)=21 | | 8x-52=x | | 11x-9=8x+6 | | 9g^2+g=0 | | -7/3(y-12)-1/9y | | C-7.2=12 | | 3x^2+36x-8=0 | | 3x^2=19x+14 | | 13=-2+c | | y=ln(x^4+e^2x) | | 4*sin*2x-1=-5 | | -4b^2+81=0 | | 3(20+h)=1 | | f(x)=ln(x^4+e^2x) | | -24=-10a | | p=2m+n | | 2x-(-x+5)=6+(x+1) | | 11=h+3 | | 43o+8+6o=-90 | | 2(50-x)=40 | | -4=y/5 | | -25x-17=12x-8 |